Myeloid Fmr1 deficiency in mice results in reduced serum cholesterol and altered bile pathway gene expression - Xiaoning Zhao; Jianchang Zhou; Kuang-Yuh Chyu; Ebru Erbay; Bojan Cercek; Prediman K. Shah; Paul C. Dimayuga (PLoS ONE, 2026)
Fragile X Syndrome (FXS) is a genetic disorder caused by increased CGG repeats in the Fragile X Messenger Ribonucleoprotein 1 (FMR1) gene which encodes an RNA-binding protein that can alter mRNA processing, translation and stability. Among the effects of FMRP deficiency is the modulation of metabolic pathway gene expression resulting in reduced cholesterol. In this report, the role of Fmr1 in modulating serum cholesterol of mice fed Western diet was investigated. Fmr1-KO mice had reduced serum cholesterol that occurred even as LDLR expression was reduced, suggesting a non-LDLR pathway of cholesterol clearance. Hepatic bile synthesis gene expression was altered in the Fmr1-KO mice. Given the reports of myeloid cell modulation of liver function, myeloid specific Fmr1 deficiency was investigated. Reduced serum cholesterol was replicated in myeloid-specific deficiency of Fmr1. Myeloid-specific deficient Fmr1 female mice had significantly increased Cyp27a1 while male mice had significantly increased Cyp7b1, yet no differences were observed in serum bile acid levels. Evaluation of bile transporter expression demonstrated that female mice with myeloid Fmr1 deficiency had significantly increased expression of Ntcp and Slco1b2, while myeloid Fmr1 deficient male mice had significantly increased Slco1a1. The sulfonating enzyme Sult2a8 was increased in both female and male mice suggesting some commonality in the pathway, but over-expression of Sult2a8 in Western diet fed wild type mice did not alter serum cholesterol. However, liver expression of the bile acid membrane G protein coupled receptor Tgr5 was significantly increased in myeloid Fmr1 deficient mice suggesting a novel interaction between the Fmr1 gene and Tgr5.